2016
DOI: 10.1111/jhn.12382
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional intervention as part of functional rehabilitation in older people with reduced functional ability: a systematic review and meta‐analysis of randomised controlled studies

Abstract: This meta-analysis highlights concerns regarding the quality of the randomisation of participants at baseline. Future high-quality research is essential to establish whether older people with loss of functional abilities can benefit from nutritional intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 32 publications
1
18
1
Order By: Relevance
“…On the contrary, the FIM and home discharge were not affected by whether or not RDs were assigned. This finding is consistent with previous studies regarding nutritional intervention, indicating that even when performed with rehabilitation, nutritional intervention did not improve functional recovery (21,22). Additionally, the effect of assignment of RDs on BMI gain (0.1 kg/ m 2 ) was lower than the minimum clinically important difference of BMI (0.7 kg/m 2 ) (23).…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, the FIM and home discharge were not affected by whether or not RDs were assigned. This finding is consistent with previous studies regarding nutritional intervention, indicating that even when performed with rehabilitation, nutritional intervention did not improve functional recovery (21,22). Additionally, the effect of assignment of RDs on BMI gain (0.1 kg/ m 2 ) was lower than the minimum clinically important difference of BMI (0.7 kg/m 2 ) (23).…”
Section: Discussionsupporting
confidence: 91%
“…Although there are some differences in background between their review and the present review, nutritional supplementation tends to improve handgrip strength significantly. With regard to reviews that investigated the effects of nutritional intervention combined with rehabilitation, these found no significant improvements in ADL (Beck et al ., Collins et al Collins et al …”
Section: Discussionmentioning
confidence: 99%
“…These have suggested that energy and protein intake can be improved (Abbott et Baldwin and Weekes, 2011;Collins and Porter, 2015;Milne et al, 2009a;Poscia et al, 2018) but have unfortunately not shown clear results for functional or clinical outcomes. Indeed, several reviews have commented on the weaknesses in methodological design of primary studies which result in inconclusive results (Beck et al, 2016). These include a lack of consistency in the assessment of function, meaning meta-analysis is not possible, lack of power due to small sample size leading to a risk of type-2 errors, differences in the amount and composition of nutrients included in the supplement, inclusion of well-nourished persons who are less likely to benefit from treatment, and high risk of bias and differences in baseline measures between groups (Beck et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several reviews have commented on the weaknesses in methodological design of primary studies which result in inconclusive results (Beck et al, 2016). These include a lack of consistency in the assessment of function, meaning meta-analysis is not possible, lack of power due to small sample size leading to a risk of type-2 errors, differences in the amount and composition of nutrients included in the supplement, inclusion of well-nourished persons who are less likely to benefit from treatment, and high risk of bias and differences in baseline measures between groups (Beck et al, 2016). Other reviews have also only examined specific population groups (e.g.…”
Section: Introductionmentioning
confidence: 99%